Regional Lobar Atrophy Predicts Memory Impairment in Multiple Sclerosis - Benedict, Ralph H. B.; Zivadinov, Robert; Carone, Dominic A.; Weinstock-Guttman, Bianca; Gaines, Jeff; Maggiore, Cosimo; Sharma, Jitendra; Tomassi, Maria-Antonietta; Bakshi, Rohit (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: In recent studies, measures of whole brain atrophy were strongly correlated with neuropsychological testing, explaining more variance than measures of lesion burden in patients with multiple sclerosis. The relationship between regional lobar atrophy and cognitive impairment is yet to be examined. We endeavored to assess the clinical significance of regional lobar atrophy in multiple sclerosis.METHODS: In a cross-sectional study, we evaluated 31 patients with multiple sclerosis with brain MR imaging and neuropsychological testing. Impairment was determined by comparison with demographically matched healthy controls. MR imaging generated measures of lesion burden (fluid-attenuated inversion recovery hyperintense volume), general atrophy (brain parenchymal fraction), central atrophy (lateral ventricle volume), and lobar atrophy (regional brain parenchymal fraction of frontal, temporal, parietal, and occipital lobes in each hemisphere). Neuropsychological testing emphasized measures of processing speed and memory, because these are commonly affected in multiple sclerosis.RESULTS: Patients with multiple sclerosis showed significant atrophy and impairment on all neuropsychological tests. Regional atrophy accounted for the most variance in all regression models predicting memory performance. Left temporal atrophy was the primary predictor of auditory/verbal memory (partial r’s = 0.55–0.61), and both left and right temporal atrophy predicted visual/spatial memory performance (partial r’s = 0.51–0.67). Models predicting learning consistency retained frontal lobe atrophy measures (partial r’s = 0.44–0.68). Central and general atrophy measures were the primary predictors in modeling processing speed (partial r’s = 0.42–0.64).CONCLUSION: Regional atrophy accounts for more variance than lesion burden, whole brain atrophy, or lateral ventricle volume in predicting multiple sclerosis–associated memory dysfunction.